2018
DOI: 10.1088/1612-202x/aac003
|View full text |Cite
|
Sign up to set email alerts
|

Formation of hemoglobin photoproduct is responsible for two-photon and single photon-excited fluorescence of red blood cells

Abstract: Two-photon excited fluorescence of red blood cells (RBC) has been reported to be applicable for their assessment in vitro and in vivo. The corresponding fluorescence emission was ascribed to hemoglobin (Hb), however, as Hb is essentially non-fluorescent at single-photon excitation, the mechanism of two-photon excited fluorescence of RBC remains debatable. Here we show that a fluorescent photoproduct, characterized by an ultrafast decay of excitation, is formed after irradiation of Hb with femtosecond laser pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…They are localized in the proximity of blood capillaries, which are visible in dark red in the TPE-FLIM images (Fig. 6b, d, f) due to ultrafast fluorescence decay of Hb photoproducts 59 . The presence of cytoplasmic granules is a specific hallmark feature of MCs.…”
Section: Discussionmentioning
confidence: 99%
“…They are localized in the proximity of blood capillaries, which are visible in dark red in the TPE-FLIM images (Fig. 6b, d, f) due to ultrafast fluorescence decay of Hb photoproducts 59 . The presence of cytoplasmic granules is a specific hallmark feature of MCs.…”
Section: Discussionmentioning
confidence: 99%
“…In [51] the authors propose the usage of green endogenous AF as a real-time quantification of cellular senescence in human mesenchymal stromal cells based on label-free flow cytometry analysis and the involvement of lipofuscin in the AF increase was discussed. In our previous work it was shown that the appearance of the fluorescence signal in the living cells can be governed by the formation of photoproducts: for instance, the irradiation of erythrocytes with 760 nm femtosecond laser pulses led to the formation of hemoglobin photoproducts which were characterized by a broad excitation spectrum [52].…”
Section: Discussionmentioning
confidence: 99%
“…Further studies revealed that single (in the 400-500 nm range) and two-photon excited fluorescence of RBC is due to the formation of Hb photoproduct [29]. As a consequence, fluorescence intensity of RBC suspension and Hb aqueous solution increases linearly with the irradiation time [29].…”
Section: Autofluorescence Of Red Blood Cellsmentioning
confidence: 96%